2012
DOI: 10.1186/ar3911
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in cytochrome P450 2C19 enzyme and cessation of leflunomide in patients with rheumatoid arthritis

Abstract: IntroductionRational selection of disease modifying anti-rheumatic drugs in the treatment of rheumatoid arthritis (RA) has many potential advantages, including rapid disease control, reduced long-term disability and reduced overall cost to the healthcare system. Inter-individual genetic differences are particularly attractive as markers to predict efficacy and toxicity, as they can be determined rapidly prior to drug selection. The aims of this study, therefore, were to investigate the association between diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…In fact, the mitochondrial membrane potential of primary rat hepatocytes did show more sensitive to LEF than Figure S1). Many reports demonstrated that the polymorphism of several CYPs, such as CYP1A2 and CYP2C19, could affect the liver toxicity of LEF in patients with rheumatoid arthritis [24][25][26] , which could be indirect evidences that CYPs play a critical role in the detoxification of LEF in the body. Our studies with HRN mice are the first direct in vivo evidences that hepatic CYPs are involved in the clearance and toxicity of LEF.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the mitochondrial membrane potential of primary rat hepatocytes did show more sensitive to LEF than Figure S1). Many reports demonstrated that the polymorphism of several CYPs, such as CYP1A2 and CYP2C19, could affect the liver toxicity of LEF in patients with rheumatoid arthritis [24][25][26] , which could be indirect evidences that CYPs play a critical role in the detoxification of LEF in the body. Our studies with HRN mice are the first direct in vivo evidences that hepatic CYPs are involved in the clearance and toxicity of LEF.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of hepatotoxicity with teriflunomide may be lower than with the parent leflunomide. Leflunomide is metabolized to teriflunomide by CYP enzymes, including CYP2C19, and it has been shown that toxicity of leflunomide appears to be related to CYP2C19 phenotype, with poor metabolizers having an increased rate of toxicity [81]. In addition, in vitro studies have shown that leflunomide-mediated hepatotoxicity can be inhibited by administration of a pan CYP enzyme inhibitor and that hepatotoxicity is related to hepatic activation of leflunomide, possibly via the formation of a toxic metabolite.…”
Section: Safety and Tolerabilitymentioning
confidence: 98%
“…The one caveat is that other drugs used concurrently with leflunomide for RA, notable methotrexate, may have a synergistic effect at causing these adverse reactions, in particular nausea, neutropenia, alopecia and pneumonitis. However, there is some preliminary evidence to suggest that hepatotoxicity may be less common with teriflunomide compared with leflunomide [80,81], while opportunistic infections and effects in pregnancy are worthy of special consideration.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Leflunomide is metabolized by polymorphic phase I enzymes, particularly CYP1A2 (cytochrome P450 1A2), CYP2C and CYP3A4 (cytochrome P450 3A4), but studies [66][67][68][69][70][71] addressing the role of altered metabolism genetically determined and the risk of developing hypersensitivity reactions to leflunomide are still insufficient.…”
Section: Recent Advances In Genetic and Metabolic Biomarkers Of Hypermentioning
confidence: 98%